Yield response and validation of CROPWAT for baby corn under drip irrigation - KUMAR, MUKESH; KUMAR, ROHITASHW (Journal of Soil and Water Conservation, 2023)
A study was conducted in 2020-21 to evaluate the optimal irrigation levels for maximum baby corn production with CROPWAT irrigation model using the data for baby corn cultivation round the year (three season). The irrigation was applied alternative days at three system operating pressures such as 0.5 kg cm-2; 1.0 kg cm-2 and 1.5 kg cm-2 using drip irrigation replicated three times. The irrigation water requirement along with scheduling of baby corn crop was determine using FAO-CROPWAT 8.0 software. The crop water requirement during three seasons i.e. 1, 2 and 3 were found 22.4, 60.7 and 61.7 mm, respectively. The results of data analysis showed that yield of baby corn was not significantly (P